Determination of T-2 and HT-2 Toxins in Seed of Milk Thistle [Silybum marianum (L.) Gaertn.] Using Immunoaffinity Column by UPLC-MS/MS - Boško, Rastislav; Pernica, Marek; Běláková, Sylvie; Bjelková, Marie; Pluháčková, Helena (Toxins, 2022)
Milk thistle [Silybum marianum (L.) Gaertn.] achieved a significant increase in interest over the past few years from local and foreign pharmaceutical corporations. The silymarin complex of constituents extracted from milk thistle achenes provides compelling health benefits primarily thanks to antioxidant activities and hepatoprotective effects. However, consuming mycotoxin-contaminated plant material can cause immunosuppression and hepatotoxic problems. The aim of this study was to develop and validate a method for the determination of mycotoxin content in milk thistle. Fusarium toxins as T-2 and HT-2 toxins in grown milk thistle harvested from a breeding station in the Czech Republic during 2020-2021 were studied. The analysis of T-2 and HT-2 toxins was performed by UPLC-MS/MS after immunoaffinity columns EASI-EXTRACT® T-2 & HT-2 clean up. All analysed samples of milk thistle were contaminated with T-2 toxin and HT-2 toxin. The content of T-2 toxin in the samples from 2020 was in the range of 122.7-290.2 µg/kg and HT-2 toxin 157.0-319.0 µg/kg. In 2021, the content of T-2 toxin was in the range of 28.8-69.9 µg/kg and HT-2 toxin was 24.2-75.4 µg/kg. The results show that the climatic conditions of the year of harvesting have a highly statistically significant effect on the content of T-2 and HT-2 toxins in milk thistle.
Keywords: immunoaffinity column; antioxidancia; flavonoidy; Flavonoids; Chromatography, High Pressure Liquid; UPLC-MS/MS; Chromatography, Liquid; Seeds; silymarin; Antioxidants; šlechtění rostlin; T-2 Toxin; tandemová hmotnostní spektrometrie; Silymarin; mykotoxiny; vysokoúčinná kapalinová chromatografie; Biological Products; semena rostlinná; T-2 toxin; Plant Breeding; Tandem Mass Spectrometry; chromatografie kapalinová; ostropestřec mariánský; milk thistle; validation method; Silybum marianum; biologické přípravky; Mycotoxins; HT-2 toxin